Faktor-faktor yang mempengaruhi prestasi akademik remaja - Munjirin, Ahmad; Iswinarti, Iswinarti (Universitas Muhammadiyah Malang, 2023)
Academic achievement plays a crucial role in an individual's life. This study aims to examine the factors that influence academic achievement using the systematic review method. By gathering and analyzing data from various relevant studies, this research aims to enhance accuracy, comprehensive understanding, and knowledge updates, and identify research areas that have not been addressed in relation to factors affecting academic achievement. The study's results, which includes 11 research journals, indicate that factors such as motivation, social support, study habits, cognitive ability, and learning environment significantly impact academic achievement. This research provides valuable guidance for individuals, parents, teachers, and other stakeholders in comprehending the factors that influence academic achievement. Furthermore, it also serves as a foundation for the development of more effective education policies.Keywords: Academic achievement, adolescents, systematic review